Questions of (Mis)Recognition in the Relationship Between Italian Teachers and Asylum-Seeker Students - Oshodi, Darasimi Powei (INSTED: Interdisciplinary Studies in Education & Society, 2021)
The potential of the classroom as a relational space for the development of a positive sense of self by asylum seekers has received scant attention in literature. My PhD research explores this potential using Honneth’s theory of recognition. In this paper, I work on a small part of my study, involving three teachers from an adult education centre in Italy. By employing narrative inquiry, I search for clues of recognition in the teachers’ narratives about their perceptions and values, relationships with learners, and understanding and concern for learners.